Emerging research surrounding power consumption and performance issues in utility computing - Deka, Ganesh Chandra 1969-; Siddesh, G.M; Srinivasa, K.G; Patnaik, L.M (Advances in systems analysis, software engineering, and high performance computing (ASASEHPC) book series, 2016)
This book explores methods of treating computing resources and materials as a standard utility, charging customers based on their usage and promoting competition among service providers, covering both benefits and hindrances, as well as theoretical concepts and practical considerations